PENGEMBANGAN MEDIA PEMBELAJARAN MATH BOX MATA PELAJARAN MATEMATIKA MATERI SIFAT-SIFAT BANGUN DATAR KELAS IV SD: Pengembangan Media - Rizki Dwisafitri; Singgih Adhi Prasetyo; M. Yusuf Setia Wardana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop a learning medium called Math Box, designed as an enjoyable instructional and game-based tool to help fourth-grade elementary school students learn the properties of two-dimensional shapes. The research employed a Research and Development (R&D) approach using the ADDIE model. The Math Box media was validated by media experts and material experts before being tested on fourth-grade C students at SDIT Rabbani Kendal. The media expert validation resulted in a feasibility score of 98%, categorized as feasible. Material expert validation was conducted in three stages, showing progressive improvements with scores of 52%, 72%, and 96%, and was ultimately deemed highly feasible. A limited field trial indicated a teacher response score of 96% and a student response score of 95%, both categorized as very practical. These findings demonstrate that Math Box can enhance students’ interest and create a more active learning environment. Therefore, Math Box is considered suitable for use as a mathematics learning medium for teaching two-dimensional shapes.